Efektivitas Program Jakarta Entrepreneur untuk Mengurangi Angka Pengangguran: (Studi Kasus di Kota Jakarta Selatan) - Diana Azzahra; Abdul Rahman (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to assess the effectiveness of the Jakpreneur program in reducing unemployment in South Jakarta. Jakpreneur is a strategic initiative launched by the Jakarta Provincial Government as a concrete effort to empower Micro, Small, and Medium Enterprises (MSMEs). This program is designed with various forms of support, such as skills training, business mentoring, legal licensing facilitation, product marketing support, and easy access to capital. This aims to create an inclusive and sustainable entrepreneurial ecosystem, especially amidst the complex challenges of the urban economy and the ongoing unemployment rate. However, in its implementation on the ground, the program's effectiveness still faces several obstacles. One of the main problems identified is the suboptimality of information technology-based training. Many participants have not yet mastered basic digital skills, making it difficult to keep up with developments in training methods that rely on technology. In addition, the low level of responsiveness of program facilitators to participant needs, as well as the limited digital literacy of MSMEs, also hinders maximizing the benefits of this program. This study uses a descriptive qualitative approach with data collection techniques through in-depth interviews, participant observation, and documentation studies. The findings indicate that, despite some shortcomings, the Jakpreneur program has been generally successful in improving participants' entrepreneurial knowledge and skills, reaching the right target audience, and having a tangible impact on increasing business capacity and reducing unemployment. Therefore, strengthening outreach, improving the quality of digital training, and providing more active and responsive mentoring is necessary to further enhance the program's effectiveness.